(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
The study determined universal basic education board’s preparation of periodic master plans for balanced and co-ordinated development of universal basic education programme in Imo state. One research question and one null hypothesis guided the study. The study adopted the descriptive survey research design. The population of the study comprised of 304 staff of IMSUBEB. The instrument for data collection was a questionnaire titled ‘State Universal Basic Education Board’s Preparation of Periodic Master Plans for Balanced and Co-ordinated Development of Universal Basic Education Questionnaire’ which was validated by three experts. The reliability of the instrument was established using Cronbach Alpha which yielded a coefficient of 0.88. The instrument was administered on the respondents by the researchers with the help of 10 research assistants. The data relating to research questions were answered using frequency count, and weighted response average while the hypothesis was tested using z-test. The findings of the study revealed among others that: Universal Basic Education Board performs to a high extent, the function of preparing periodic master plans for a balanced and coordinated development of Universal Basic Education Programme. There was also a significant difference in the mean ratings of board members and head-teachers on the Board’s preparation periodic master plans for a balanced and coordinated development of Universal Basic Education Programme in Imo state. It was therefore recommended that the Board should create and apply a comprehensive set of evaluation criteria that includes both strategic goals and operational effectiveness to assess the success of master plans. They should develop an evaluation framework that integrates feedback from various stakeholders and considers both the strategic and practical aspects of master planning.